2020
DOI: 10.2147/bctt.s268926
|View full text |Cite
|
Sign up to set email alerts
|

<p>Inhibition of Yes-Associated Protein-1 (YAP1) Enhances the Response of Invasive Breast Cancer Cells to the Standard Therapy</p>

Abstract: Purpose The deregulation of the Hippo pathway results in translocation ofYes-associated protein-1 (YAP1) to the nucleus to exert an oncogenic effect. This effect has been demonstrated in several malignancies, yet, in breast cancer (BC), it remains controversial. The present study aimed to investigate the significance of YAP1 expression in BC, its relation to cancer stem cells (CSCs), and the effect of its inhibition on tumor cell survival. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…23 YAP1 functioned as an oncogene to promote breast cancer survival, 24 and repression of YAP1 contributed to suppression of breast cancer progression. 25,26 YAP1 was reported to be the target of STUB1 in gastric cancer cells, 27 and our results showed that forced STUB1 attenuated TRIM6-induced increase in YAP1. In addition, knockdown of TRIM6 repressed in vivo breast cancer growth through increasing of STUB1 and decreasing of YAP1.…”
Section: Discussionsupporting
confidence: 62%
“…23 YAP1 functioned as an oncogene to promote breast cancer survival, 24 and repression of YAP1 contributed to suppression of breast cancer progression. 25,26 YAP1 was reported to be the target of STUB1 in gastric cancer cells, 27 and our results showed that forced STUB1 attenuated TRIM6-induced increase in YAP1. In addition, knockdown of TRIM6 repressed in vivo breast cancer growth through increasing of STUB1 and decreasing of YAP1.…”
Section: Discussionsupporting
confidence: 62%
“…CRC is caused by multiple factors and multiple mechanisms, which are associated with abnormal cell signaling pathways, such as the Hippo/Yes-associated protein 1 (YAP1) pathway and the Wnt/β-catenin pathway (3,4). In the Hippo/YAP1 signaling pathway, the activation of YAP1 is associated with tumor acquisition of malignant characteristics, including anti-cancer therapy resistance, the metastasis of cancer stem cells, and epithelial-mesenchymal transformation (5)(6)(7). In addition, YAP1 has been shown to be associated with poor prognosis and reduced survival in many human cancers (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…[37] The mRNA level of YAP and its receptors is also elevated in breast cancer compared with that in normal breast tissues. [38] Some functional regions of YAP bind to Kruppel-like factor 5 (KLF5), a transcription factor that promotes breast cell proliferation and survival, thereby regulating cell proliferation. [12] The current meta-analysis of this study, however, indicated contradictory results between non-TNBC and TNBC by summarizing 10 case-control studies.…”
Section: Discussionmentioning
confidence: 99%